KAJIAN YURIDIS PERATURAN MENTERI KESEHATAN REPUBLIK INDONESIA NOMOR 35 TAHUN 2014 TENTANG STANDAR PELAYANAN KEFARMASIAN DI APOTEK - Deddy Rusdiana; andry Priyoheriyanto (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2023)
Regulation of the Minister of Health of the Republic of Indonesia Number 35 of 2014 concerning Pharmaceutical Service Standards in Pharmacies is a regulation that contains service standards that must be met by pharmacies in providing pharmaceutical services to the public. This regulation aims to improve the quality of pharmaceutical services in pharmacies and ensure that medicines sold and distributed to the public are safe, effective and useful. However, there are several problems related to the implementation of the Regulation of the Minister of Health of the Republic of Indonesia Number 35 of 2014 concerning Pharmaceutical Service Standards in Pharmacies. First, there are still many pharmacies that do not meet the pharmaceutical service standards stipulated in the regulation. Some pharmacies still sell drugs without a doctor's prescription, provide drugs that have expired, and do not provide sufficient information to patients regarding drug use. a juridical study is needed that aims to evaluate the implementation of the Regulation of the Minister of Health of the Republic of Indonesia Number 35 of 2014 concerning Pharmaceutical Service Standards in Pharmacies and find solutions to overcome problems related to its implementation. So that it still needs improvement and improvement in terms of understanding, resources, and supervision. The proposed solutions can be a first step in addressing these issues and ensuring more effective enforcement of regulations in the future.